2021
DOI: 10.3390/healthcare9091149
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Botulism in Western Romania: Ten Years’ Experience at a Tertiary Infectious Disease Hospital

Abstract: Objectives: The purpose of this study was to analyze epidemiological data concerning foodborne botulism in Western Romania over the last decade. Botulism, the toxin formed by the bacterium Clostridium botulinum, results in a neuroparalytic disorder capable of severe clinical progression that begins in the cranial nerves and progressively descends. Preventing progression to a severe case entails timely diagnosis since curative assets are restricted. Ingesting food containing a preformed toxin (foodborne botulis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
1
0
3
Order By: Relevance
“…From the descriptive analysis of the data reported for 2007-2020, it was observed that botulism cases in Romania occurred every year, with a median of 22 cases per year. Both isolated cases and outbreaks have been reported [26]. The maximum number of cases was reported in 2007, when Romania ranked second in Europe in terms of number of reported cases, after Poland [27].…”
Section: Discussionmentioning
confidence: 99%
“…From the descriptive analysis of the data reported for 2007-2020, it was observed that botulism cases in Romania occurred every year, with a median of 22 cases per year. Both isolated cases and outbreaks have been reported [26]. The maximum number of cases was reported in 2007, when Romania ranked second in Europe in terms of number of reported cases, after Poland [27].…”
Section: Discussionmentioning
confidence: 99%
“…Botulizmo eigos sunkumas priklauso nuo paciento individualių savybių ir nuo į organizmą patekusio toksino tipo ir kiekio [4]. Ligos eiga gali būti lengva, kai pasireiškus pirmiesiems simptomams, naujų nebeatsiranda, o esantys palaipsniui išnyksta [2].…”
Section: Tyrimo Rezultataiunclassified
“…Regėjimo sutrikimai apima neryškų vaizdą, dvejinimąsi akyse, oftalmoplegiją ir ptozę [3]. Botulizmas gali pasireikšti vangiuoju gerklės ir ryklės raumenų paralyžiumi [4]. Dėl šio paralyžiaus ankstyvas kvėpavimo funkcijos sutrikimas gali būti ne dėl kvėpavimo raumenų parezės, bet dėl viršutinių kvėpavimo takų sukritimo ar sekretų kaupimosi [3].…”
Section: Botulizmo Klinikinis Pasireiškimas Donata Pakeltytėunclassified
See 1 more Smart Citation